Caterflies and ice - Citro, Asia; Lindsay, Marion (Seattle, WA : The Innovation Press, 2017)
"When an unexpected snowstorm causes trouble for the magical creatures of the forest, Zoey and Sassafras come to the rescue. But their first attempt to save trapped caterfly eggs results in a big mistake. Can they figure out a way to fix things before the baby caterflies hatch?"-- book jacket.
Grades K-5.
600L
Decoding demand: 80 (high) Semantic demand: 97 (very high) Syntactic demand: 88 (very high) Structure demand: 87 (very high)
Keywords: Cats -- Juvenile fiction; Snow -- Juvenile fiction; Science -- Experiments -- Juvenile fiction; Rescues -- Juvenile fiction; Imaginary creatures -- Fiction